Pengukuran Kinerja Perusahaan dengan Konsep Balanced Scorecard (Studi Kasus pada Bank Nagari) - Susriyanti, Susriyanti (Jurnal Ekonomi, 2013)
This study aimed to analysis performance measurement of firm by balanced scorecard methode in Bank Nagari. Research object is Bank Nagari with two performance measurement aspect consist of financial and non financial. Samples are employee of Bank Nagari taked by purposive sampling methode at least 18 respondents. Samples criteria are work periode 10 years, level management, and located in center office of Bank Nagari Padang. Analysis methode used to measure performance with balanced scorecard and qualitative analysis. Overall, the result shows that financial, customer, internal business process, learning and growth perspectives are significant growth in Bank Nagari performance.